Experimental investigations and field applications of a tension estimation method for two linked suspenders using only local vibration measurements - Wen-Hwa Wu; Chien-Chou Chen; Meng-Xuan Wu; Gwolong Lai (Results in Engineering)
Traditional vibration-based tension estimation methods are primarily developed for individual stay cables or suspenders, with limited direct applicability to physically linked cable systems. This study advances a mode shape-enhanced approach using local vibration measurements to estimate the tensions of two suspenders connected by an intersection clamp. The methodology is validated through both laboratory experiments and field measurements, with particular emphasis on practical applicability. Laboratory tests on linked steel strands explore the influence of different clamp configurations and slenderness parameters. Results confirm that employing plastic spring clamps improves estimation accuracy for in-plane modes compared to that of C-clamps. Tension estimation errors are kept below 0.5% when the slenderness parameter exceeds 600, and rise to 2% to 3% as it approaches 250. To improve estimation robustness under field conditions, a regression-based mode screening algorithm is introduced. This algorithm refines the selection of vibration modes based on regression consistency rather than fixed thresholds. Field measurements conducted on the Shing-Tong Bridge demonstrate that the proposed method remains reliable despite complex spectral characteristics. For one linked suspender, the estimated tension errors are approximately −3% (out-of-plane) and 1% (in-plane). For another suspender with full sensor coverage, the error is held below 1%. The study demonstrates that accurate and stable tension estimation is achievable for physically linked suspender systems using a practical deployment scheme. The proposed framework offers a scalable solution for long-term monitoring of arch bridge suspender networks under real-world constraints.